Assessment of antimicrobiral prophylaxis in transperineal prostate biopsy: A single-center retrospective study of 485 cases. Issue 8 (August 2018) - Baba, Kyoko; Sekine, Yoshitaka; Miyazawa, Yoshiyuki; Syuto, Takahiro; Nomura, Masashi; Koike, Hidekazu; Matsui, Hiroshi; Shibata, Yasuhiro; Ito, Kazuto; Suzuki, Kazuhiro
Abstract: To verify the validity of our antimicrobial prophylaxis regimen for transperineal prostate biopsies, we investigated the rate of infectious complications in this procedure. We retrospectively investigated the infectious complications in 485 patients who underwent a transperineal prostate biopsy between 2014 and 2016 at our hospital. In the clinic, we use cefazolin (CEZ) for antimicrobial prophylaxis. Infectious complications were assessed up to postoperative day (POD) 30. Patients with infectious complications were further investigated to determine the site of infection, outbreak day, and type of pathogenic bacteria. The rate of infectious complications was 0.82% (4 out of 485 patients). Three patients developed prostatitis, 1 progressed into septic shock, and 1 patient developed epididymitis. The pathogenic bacteria identified were Pseudomonas aeruginosa (1 of 4), Enterococcus faecalis (1 of 4) and Escherichia coli that harbour extended-spectrum beta lactamase (ESBL-productive E. coli ) (2 of 4). The earliest outbreak was POD 2 and the latest was POD 14. Infectious complications tended to increase in patients in whom an indwelling urethral catheter was inserted ( p  = 0.0567). However, there were no statistically significant relationships between any risk factor and the occurrence of infectious complications. We concluded that CEZ is adequate for the prevention of perioperative infectious complications in transperineal prostate biopsies. Furthermore, we reaffirmed the importance of correct perioperative management, including preoperative assessment.